2012
DOI: 10.2174/138161212803832308
|View full text |Cite
|
Sign up to set email alerts
|

Fospropofol, A New Sedative Anesthetic, and Its Utility in the Perioperative Period

Abstract: Fospropofol is an intravenous sedative-anesthetic agent that is FDA-approved for monitored anesthesia care (MAC) sedation in adult patients undergoing diagnostic or therapeutic procedures. As a prodrug of propofol, fospropofol's pharmacologic activity results from its breakdown by alkaline phosphatase and release of propofol, which is the active molecule. It exhibits a longer time to peak clinical effect and a more prolonged action compared to propofol. Thus patients may exhibit smoother hemodynamic and respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…An increasing number of recent studies have shown that MAC with laryngeal mask ventilation has unique advantages for outpatient flexible bronchoscopy management (18). It provides appropriate operating conditions for the bronchoscopist and accelerates recovery (19,20). Intravenous infusion of propofol and remifentanil combined with dexmedetomidine has been used for flexible bronchoscopy in previous reports (13).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of recent studies have shown that MAC with laryngeal mask ventilation has unique advantages for outpatient flexible bronchoscopy management (18). It provides appropriate operating conditions for the bronchoscopist and accelerates recovery (19,20). Intravenous infusion of propofol and remifentanil combined with dexmedetomidine has been used for flexible bronchoscopy in previous reports (13).…”
Section: Discussionmentioning
confidence: 99%
“…It cannot only provide excellent operating conditions for the bronchoscopist but also accelerate children rapid recovery. [16,20] Previously, benzodiazepines are one of the most commonly used drugs during flexible bronchoscopy. They play the role of muscle relaxant besides sedative, hypnotic and anxiolytic though the γ-aminobutyric acid receptor.…”
Section: Discussionmentioning
confidence: 99%
“…For prodrugs, due to the existence of enzymatic and/or chemical transformation processes, the therapeutic effects of the parent drug are usually delayed. Since the enzymatic conversion to propofol is timedependent, fospropofol may theoretically provide a better safety profile, especially in cardiac and respiratory functions (Abdelmalak et al, 2012). For example, recent studies have shown a decreased incidence of hypotension and respiratory depression with fospropofol because of its slower onset of action (Luo et al, 2022).…”
Section: Phosphate Prodrugsmentioning
confidence: 99%